Analysis of plated-hull structure strength against hydrostatic and hydrodynamic loads: A case study of 600 TEU container ships - Akbar Muhammad Sabiqulkhair (De Gruyter, 2021)
The assessment of a ship's ability to withstand environmental loads is very crucial. This research focuses on the strength assessment of 600 TEU container ship hulls against hydrostatic and hydrodynamic loads using finite element-based software. Parameter changes in the material types, hull thickness, and ship drafts were performed to compare the structural responses using deformation, strain, and von Mises stress criteria. All of the materials tested were acceptable, where the ASTM A131 Grade AH36 and ASTM A131 Grade AH32 materials have the lowest deformation values and strains. The simulation results regarding plate thickness variation, deformation, strain, and von Mises stress values were smaller as the thickness of the ship structure increased. Moreover, from the draft variation, the structural response due to environmental load was better as the draft of the ship increased.